The Factors That Influence the Level of Underpricing of Shares in Non-Financial Companies That Conduct IPO (Initial Public Offering) on the Indonesian Stock Exchange - Minawati Dewi; Sadikin, Ali; Fahmi Roy Dalimunthe (HM Publisher, 2024)
Underpricing is also often defined as the positive difference between the share price in the secondary market and the share price in the primary market or during the initial public offering (IPO). This price difference is known as the initial return (IR) or positive return for investors. Underpricing is a common phenomenon that often occurs in the capital market and when companies conduct an initial public offering (IPO). This research was conducted to analyse the factors that affect the level of stock underpricing in non-financial companies. These factors are Return on assets, financial leverage, underwriter reputation, and company size. The population of this study is non-financial companies that conducted IPOs on the Indonesia Stock Exchange in 2015-2019. Sampling using purposive sampling, namely sample selection with certain criteria, so that 30 companies were obtained as research samples. The research method uses multiple linear regression, classical assumption test, t test and f test. The results showed that only company size has a significant effect on underpricing. While return on assets, financial leverage and underwriter reputation have no significant effect on underpricing. Simultaneously and significantly return on assets, financial leverage, underwriter reputation and company size affect underpricing.